Four Critiques of the Redistribution Hypothesis : An Assessment - Milanovic, Branko (2012)
This paper discusses and assesses critiques of the aurhor's reformulation of the median voter hypothesis and its testing. The author rephrases and redefines more correctly the redistribution hypothesis and clarifies its relationship with the median voter hypothesis. He also reviews four types of critiques leveled at his approach.